Liberalism : the classical tradition - Von Mises, Ludwig, 1881-1973.; Greaves, Bettina Bien. (Indianapolis : Liberty Fund, 2005)
"This book presents the theoretical and practical arguments for liberalism. Mises contrasts liberalism with other conceivable systems of social organization such as socialism, communism, and fascism. He is also more specific here than elsewhere in applying the liberal program to economic policy, domestic and foreign."--Jacket
1. The foundations of liberal policy -- 2. Liberal economic policy -- 3. Liberal foreign policy -- 4. Liberalism and the political parties -- 5. The future of liberalism -- App. 1. On the literature of liberalism -- App. 2. On the term "liberalism."
Includes bibliographical references (pages 153-157) and index.
Translated from the German.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Liberalism; Economics; Free enterprise; Libéralisme.; Économie politique; liberalism; economics; POLITICAL SCIENCE -- Political Ideologies -- Conservatism & Liberalism; Free enterprise; Economics; Liberalism; Economics; Liberalism